Evaluation of the Effect of Gas Leakage on Operation of an Optical Engine - (:unkn) unknown (AMER SOC MECHANICAL ENGINEERS, 2010)
An experimental and numerical study is carried out to evaluate the significance of gas leakage for a non-lube optically accessible internal combustion engine and to obtain estimation for the gas flow out of the combustion chamber at each engine cycle and its effect on the in-cylinder component states during optical engine's operation. Attention is paid to blow-by and circumferential flow through the gaps between the piston rings and the liner. Optical engines are typically operated without lubrication to avoid window fouling and generation of fluorescence by oil particles that interfere with laser diagnostic signals, in view of this circumstance significant blow-by is expected in optical engines due to lack of wet-seal on the cylinder walls which permits circumferential flow of gases through the piston ring pack region resulting in increased blow-by. Semi analytical model estimating the mass loss rate is incorporated into zero dimensional thermodynamic IC engine model which simulates in-cylinder processes. Predicted results are compared for leaking and non-leaking engine simulations.